2017
DOI: 10.1097/ijg.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurements After Descemet Membrane Endothelial Keratoplasty

Abstract: Correlation between the different measurement techniques was poor and showed a broad distribution of limits of agreement. Therefore, a change between the 4 techniques during follow-up is not recommended. Nevertheless, all techniques detected the IOP elevation during follow-up, requiring therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
2
20
1
1
Order By: Relevance
“…This proportion is comparable with previous reports with IOP elevation after DMEK or Descemet stripping automated endothelial keratoplasty ranging from 0% to 15.4%. 10,17,19,28,30,31 Patient populations and definitions of elevated IOP vary considerably between studies and include thresholds ranging from 21 to 30 mm Hg and/or a threshold of 10 mm Hg above preoperative baseline values. 10,17,19,28,30,31 In our study, decimal BCVA increased, whereas CCT and ECC decreased significantly from preoperative values in patients without (group A) and with (group B) IOP elevation and there was no evidence for postoperative differences between both groups over a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is comparable with previous reports with IOP elevation after DMEK or Descemet stripping automated endothelial keratoplasty ranging from 0% to 15.4%. 10,17,19,28,30,31 Patient populations and definitions of elevated IOP vary considerably between studies and include thresholds ranging from 21 to 30 mm Hg and/or a threshold of 10 mm Hg above preoperative baseline values. 10,17,19,28,30,31 In our study, decimal BCVA increased, whereas CCT and ECC decreased significantly from preoperative values in patients without (group A) and with (group B) IOP elevation and there was no evidence for postoperative differences between both groups over a 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…33,36 Maier et al reported a signi cant correlation between non-contact tonometer (NCT), iCare, and CT at months 1 and 3 postoperatively in DMEK patients, but there was no correlation between CT, GAT, and Dynamic Contour Tonometry (DCT). 10 These results may indicate that the correlation depends on the type of IOP measurement device. Hugo et al claimed that the CT measurements were less reliable after lamellar keratoplasty due to interfaces and changes in the corneal shape.…”
Section: Discussionmentioning
confidence: 93%
“… 5 The rate of IOP increase after PK is higher than after lamellar keratoplasties. 3 Different studies have shown variable incidences of elevated IOP after different keratoplasty techniques as follows: 9–37% following PK; 5 8 6.5–24% following DMEK; 9 11 and 1.3–36.1% following DALK. 12 14 This study aimed to provide new insight into the early changes in IOP in three different corneal transplantation surgeries (PK, DALK, and DMEK) and the effect of corneal parameters and ACD on IOP changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased CT did not falsely elevate the IOP, which was measured using GAT both post-DSEK 24 , 32 , 33 and post-DALK. 31 , 34 Maier et al 9 reported a significant correlation between non-contact tonometer (NCT), iCare, and CT at months 1 and 3 postoperatively in DMEK patients, but there was no correlation between CT, GAT, and Dynamic Contour Tonometry (DCT). These results may indicate that the correlation depends on the type of IOP measurement device.…”
Section: Discussionmentioning
confidence: 99%